A Joint Enterprise : Indian Elites and the Making of British Bombay - Chopra, Preeti (Book collections on Project MUSE., 2011)
It was the era of the Raj, and yet "A Joint Enterprise" reveals the unexpected role of native communities in the transformation of the urban fabric of British Bombay from 1854 to 1918. Preeti Chopra demonstrates how British Bombay was, surprisingly, a collaboration of the colonial government and the Indian and European mercantile and industrial elite who shaped the city to serve their combined interests. Chopra shows how the European and Indian engineers, architects, and artists worked with each other to design a city--its infrastructure, architecture, public sculpture--that was lite